2019
DOI: 10.1088/1361-6587/ab4339
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on nuclear reactions using a laser-accelerated proton and deuteron beam

Abstract: We report an experimental investigation on nuclear reactions using an intense, ultra-short laseraccelerated proton and deuteron beam generated by the interaction of 25 fs, 150 TW Ti: sapphire laser pulse with normal thin foils and foils containing deuterium atoms. The production of a positron-emitting short-lived 11 C radio-isotope from the interaction of protons and deuterium ions with a solid boron palette by means of 11 B (p, n) 11 C and 10 B (d, n) 11 C nuclear reactions was studied. The maximum radioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Since 2005, there have been a series of laser-driven p-11 B experiments at several diferent facilities (Labaune et al [23,24], Picciotto et al [25], Margarone et al [26], Baccou et al [27], Tayyab et al [28], Giufrida et al [29], Margarone et al [30], Bonvalet et al [31], TPW [32], Margarone et al [33]) and the measured alpha particle yields have shown an impressive increase, as seen in Figure 3. A common goal of these experiments has been to maximize the generation of high-energy protons via laser-driven charged particle acceleration (CPA) and to interact these protons with boroncontaining targets to generate alpha particles via the p-11 B reaction.…”
Section: Alpha Yields From Laser-driven Experiments With Boron Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2005, there have been a series of laser-driven p-11 B experiments at several diferent facilities (Labaune et al [23,24], Picciotto et al [25], Margarone et al [26], Baccou et al [27], Tayyab et al [28], Giufrida et al [29], Margarone et al [30], Bonvalet et al [31], TPW [32], Margarone et al [33]) and the measured alpha particle yields have shown an impressive increase, as seen in Figure 3. A common goal of these experiments has been to maximize the generation of high-energy protons via laser-driven charged particle acceleration (CPA) and to interact these protons with boroncontaining targets to generate alpha particles via the p-11 B reaction.…”
Section: Alpha Yields From Laser-driven Experiments With Boron Targetsmentioning
confidence: 99%
“…We see that experiments have been done at a variety of wavelengths, with laser energies varying from 15 J to 1.4 kJ, laser pulse widths of 25 fs to 300 ps, and focused intensities "I" from 3 × 10 16 to 2 × 10 21 . Te experiments on the Ti : Sa laser system at the Laser Plasma Division, RRCAT, India [28] had the shortest 25 fs pulse width and focal intensities of 1 × 10 20 . Tis ensemble of experiments also encompasses a broad range of laser prepulse or contrast ratios.…”
Section: Alpha Yields From Laser-driven Experiments With Boron Targetsmentioning
confidence: 99%
“…The same case at 100 Hz is depicted by the black dashed line. The estimations for a compact laser were calculated from the single-shot experimental data reported in Tayyab et al 24 .…”
Section: Production Of 11 Cmentioning
confidence: 99%
“…Davis et al have studied theoretically neutron production from the fusion reaction of 7 Li(d, xn) [18]. Tayyab et al conducted an experimental investigation on the production of 11 C using proton and deuteron beams generated by the interaction of a 25 fs, 150 TW Ti: sapphire laser with thin foils [19], in which the highest 11 C activity obtained was 5.2 kBq per shot. Ma et al theoretically investigated the photonuclear production of 62,64 Cu at a laser intensity of 3.4 × 10 21 W cm −2 [20].…”
Section: Introductionmentioning
confidence: 99%